2022
DOI: 10.3389/fimmu.2022.913854
|View full text |Cite
|
Sign up to set email alerts
|

Integrative network analysis revealed the molecular function of folic acid on immunological enhancement in a sheep model

Abstract: We previously observed the beneficial role of folic acid supplemented from maternal or offspring diet on lamb growth performance and immunity. Twenty-four Hu lambs from four groups (mother received folic acid or not, offspring received folic acid or not) were used in the current study, which was conducted consecutively to elucidate the molecular regulatory mechanisms of folic acid in lambs by analyzing blood metabolome, liver transcriptome, and muscle transcriptome. Serum metabolomics analysis showed that L-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The existing body of published evidence strongly supports the notion that folic acid supplementation yields notable improvements in metabolic function (167), while also playing a crucial role in preventing oxidative stress and enhancing immune responses (168) in periparturient dairy cattle (169). The period around calving presents a vulnerability to lowered immunity in dairy cattle due to folic acid deficiency (165).…”
Section: Role Of Folic Acid In Mastitis Preventionmentioning
confidence: 88%
“…The existing body of published evidence strongly supports the notion that folic acid supplementation yields notable improvements in metabolic function (167), while also playing a crucial role in preventing oxidative stress and enhancing immune responses (168) in periparturient dairy cattle (169). The period around calving presents a vulnerability to lowered immunity in dairy cattle due to folic acid deficiency (165).…”
Section: Role Of Folic Acid In Mastitis Preventionmentioning
confidence: 88%
“…Isobutyrylcarnitine is a metabolic product that occurs during the transfer of acyl residues from isobutyryl coenzyme A to carnitine [ 27 ]. Previous studies have shown that higher levels of hydroxylated acylcarnitine was negatively correlated with the decline in grip strength in a short term [ 34 ], while medium and long-chain acylcarnitines were correlated with a poorer physical function [ 28 ]. Acylcarnitine, disrupting peroxisomal or mitochondrial oxidation processes [ 29 ], also plays a part in mitochondrial function, whose dysregulation is highly involved in the pathological loss of skeletal muscle mass and function in the elderly [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyodeoxycholate, androsterone sulfate and glycine have also been identified as certain specific metabolites in relation to muscle health in the current study. Hyodeoxycholate is a bile acid derivative, and a negative correlation between blood hyodeoxycholic acid and muscle uncoupling protein 3 gene was found, suggesting a potential impact on muscle function [ 34 ]. Androsterone sulfate is one metabolite of androgens, which may also be associated with the change of lean body mass and muscle mass [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the supplement of folic acid at 1.5 mg/kg significantly improved the broilers' total antioxidant capacity (T-AOC), catalase enzyme activity (CAT), and superoxide dismutase (SOD) [14]. Also, a folic acid supplement in diet was beneficial for maternal or offsprings' immune status in a sheep model [16]. Another study showed that dietary-coated folic acid improved rumen fermentation, nutrient digestibility, and growth performance in bulls [17].…”
Section: Introductionmentioning
confidence: 99%